Policy Communication Model Based on Collaborative Governance for Hydrometeorological Disaster Mitigation in West Sumatra Province - Rafeyfa Asyla Sururi; Rani Jelita Sinaga; Reni Juwita Sinaga; Sabrina Matanari Tampubulon (Contemporary Public Administration Review, 2026)
Hydrometeorological disasters constitute the dominant category of disasters in Indonesia, and West Sumatra is particularly exposed because of its geographical characteristics, environmental pressures, and changing climate conditions. Existing disaster-management arrangements involve multiple actors, yet the literature indicates continuing challenges related to fragmented coordination, one-way communication, and limited integration of local and scientific knowledge. This study aims to synthesize concepts, previous studies, and policy documents concerning policy communication and collaborative governance in hydrometeorological disaster mitigation and, on that basis, develop the Rimba Suara Policy Communication Model for West Sumatra Province. The study uses a qualitative, conceptual evidence-synthesis design based exclusively on secondary sources. A directed qualitative content-analysis approach is used because the initial analytical categories are informed by established concepts of collaborative governance, policy communication, risk communication, the pentahelix approach, and Minangkabau local wisdom. The synthesis identifies four connected requirements for a stronger policy-communication system: multi-actor coordination, accessible and dialogic risk communication, culturally grounded mediation, and continuous feedback from communities. The Rimba Suara model integrates these elements through an Attention–Interest–Search–Action–Share communication cycle. The model is presented as a conceptual proposition rather than an empirically validated intervention. Its expected contribution is to provide a theoretically grounded framework for connecting collaborative governance with risk communication and local knowledge in disaster-risk reduction. Future empirical studies are required to validate the model with stakeholders and assess its effects on trust, understanding, participation, coordination, and community resilience.